2023
DOI: 10.3389/fpubh.2023.1079319
|View full text |Cite
|
Sign up to set email alerts
|

“We are the sun for our community:” Partnering with community health workers/promotores to adapt, deliver and evaluate a home-based collaborative care model to improve equity in access to quality depression care for older U.S. Latino adults who are underserved

Abstract: BackgroundWhile depression is a leading cause of poor health, less than half of older adults receive adequate care. Inequities in both access and outcomes are even more pronounced for socially disadvantaged older adults. The collaborative care model (CCM) has potential to reduce this burden through community-based organizations (CBOs) who serve these populations. However, CCM has been understudied in diverse cultural and resource-constrained contexts. We evaluated the implementation and effectiveness of PEARLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, lower levels of family support for young breast cancer patients was significantly associated with cost‐related lack of access to care 16 . Another study evaluating a collaborative care model to improve social support for disadvantaged patients, found improvement in depression severity when patients received enhanced social support 17 . Our study is the first to specifically evaluate the impact of having an urban relative for patients physically living in rural areas.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, lower levels of family support for young breast cancer patients was significantly associated with cost‐related lack of access to care 16 . Another study evaluating a collaborative care model to improve social support for disadvantaged patients, found improvement in depression severity when patients received enhanced social support 17 . Our study is the first to specifically evaluate the impact of having an urban relative for patients physically living in rural areas.…”
Section: Discussionmentioning
confidence: 76%
“… 16 Another study evaluating a collaborative care model to improve social support for disadvantaged patients, found improvement in depression severity when patients received enhanced social support. 17 Our study is the first to specifically evaluate the impact of having an urban relative for patients physically living in rural areas. In the context of existing literature, it is a reasonable presumption that enhanced family support paired with enhanced social resources from urban relatives living physically nearer to cancer centers contributes to improved outcomes for rural patients.…”
Section: Discussionmentioning
confidence: 99%
“…This variability between outcome definitions reinforces the need for careful selection of clinically meaningful improvements by sites delivering PEARLS. Understanding the anticipated number of sessions needed to achieve clinically meaningful improvements can help sites maintain program fidelity (33) to retain PEARLS participants and ensure they receive an adequate intervention dose while reducing wait times for services (23,27,61).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated the effectiveness of PEARLS to reduce clinically significant depressive symptoms via randomized controlled trials with older adults with minor depression or dysthymia as well as adults with epilepsy and co-cooccurring major depression (24-26). Beyond this efficacy research, implementation research has been conducted to evaluate the public health impact of PEARLS via the RE-AIM Framework (27), studies have identified strategies and adaptations to make PEARLS more effective for and accessible to older adults of color, including linguistically diverse populations (28, 29). Despite the previously documented effectiveness of PEARLS, fewer studies have examined PEARLS participant attributes and program effectiveness in real-world implementations across multiple states or its ability to reduce depression using different clinical criteria including clinical remission and response.…”
Section: Introductionmentioning
confidence: 99%